Bioaktif Ekstrak Buah Pare (Momordica Charantia) dalam Regulasi Glukosa Darah dan Resistensi Insulin : Literature Review - Nurul Hikmah; Sri Julyani M; Dian Fahmi Utami (KOLONI, 2026)
Diabetes mellitus is characterized by elevated blood glucose levels exceeding the normal fasting range of 80-90 mg/dL or the non-fasting range of 140-160 mg/dL. Diabetes mellitus encompasses a group of metabolic diseases characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action, or both. The research methodology used was a literature review. This study aims to examine the function of bioactive bitter melon (Momordica charantia) fruit extract in regulating blood glucose and insulin resistance. This subject is important because of the increasing incidence of diabetes mellitus, which requires effective and safe complementary therapy solutions. The methodology used involved a literature review, analyzing 10 scientific journals sourced from the ResearchGate, PubMed, and Google Scholar databases, which were then selected according to predetermined inclusion and exclusion criteria. The analysis used a content analysis method to ensure significant conclusions. The research findings indicate that bitter melon fruit extract has considerable potential to lower blood glucose levels and improve insulin resistance due to its bioactive compounds, including charantin, polypeptide-p, flavonoids, and polysaccharides. The mechanisms include enhancing insulin sensitivity, inhibiting gluconeogenesis, and providing antioxidant and anti-inflammatory effects. Therefore, bitter melon extract has potential as a complementary therapy in the management of diabetes mellitus, although further research is needed to confirm its long-term effectiveness and safety.